The analysis of programs on posture correction for junior school-children with violation of eyesight - Вихованец (Vyhovanets S.), Світлана Василівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> The peculiarities of the usage of programs on posture correction for junior school-children with violation of eyesight are described. Publications and scientific-methodical literature on this problem are analyzed. The effectiveness of application corrective programs for children with violation of eyesight is proved. Estimated, that programs on posture correction for junior school-children with violation of eyesight in varying degrees, positively affecting the locomotorium system and physical development in general. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->